The clinical case of sildenafil administration in a very premature infant with pulmonary hypertension - Galina A. Alyamovskaya; Elena S. Keshishian; Elena G. Verchenko; Vera V. Bereznitskaya (Hygeia Press di Corridori Marinella, 2015)
We report the use of oral sildenafil in a 7-month-old preterm newborn with severe bronchopulmonary dysplasia and pulmonary arterial hypertension refractory to captopril and inhaled budesonide, and need of consistent oxygenation. Sildenafil was prepared as a powder for oral administration. Oral sildenafil treatment was continued for 11 months. Oxygen supplement was suspended after 4 months and captopril administration was finished after 7 months of sildenafil treatment. There were no adverse effects during the treatment period. The respiratory failure decreased significantly and pulmonary arterial pressure became normal after 7 months of sildenafil treatment.